2001
DOI: 10.1111/j.1752-1688.2001.tb03655.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF MULTI‐SCALE ENVIRONMENTAL CHARACTERISTICS ON AGRICULTURAL STREAM BIOTA IN EASTERN WISCONSIN1

Abstract: The U.S. Geological Survey examined 25 agricultural streams in eastern Wisconsin the determine relations between fish, invertebrate, and algal metrics and multiple spatial scales of land cover, geologic setting, hydrologic, aquatic habitat, and water chemistry data. Spearman correlation and redundancy analyses were used to examine relations among biotic metrics and environmental characteristics. Riparian vegetation, geologic, and hydrologic conditions affected the response of biotic metrics to watershed agricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
94
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 42 publications
(41 reference statements)
12
94
3
Order By: Relevance
“…On the other hand, Fitzpatrick (2001) cited by Allan (2004) described that a decline in fish IBI occurs at >30% agriculture in the catchment and only 10 %-20 % for the riparian buffer area. In the Teshio River basin most of the land use profiles at the riparian buffer scale had much higher percentage of agriculture than the designated by…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Fitzpatrick (2001) cited by Allan (2004) described that a decline in fish IBI occurs at >30% agriculture in the catchment and only 10 %-20 % for the riparian buffer area. In the Teshio River basin most of the land use profiles at the riparian buffer scale had much higher percentage of agriculture than the designated by…”
Section: Discussionmentioning
confidence: 99%
“…Fitzpatrick et al (2001) found that increasing forest cover had a negative effect on fish taxon diversity and increasing nutrient concentrations had a positive effect. Wang et al (2001) also found that an increasing percentage of agricultural land use increased fish taxon diversity, while Harding (2003) and Mensing et al (1998) found that increasing non-natural catchment land use led to a reduction in taxon diversity.…”
Section: Exploring Relationshipsmentioning
confidence: 96%
“…The endemic fish distribution pattern was also correlated with land-cover features of the catchment area. However, several studies have shown that a mixed model containing both fish habitat and landcover variables may be more effective than any individual model in explaining some of the complex fish distribution patterns (Fitzpatrick et al, 2001;Singkran and Meixler, 2008). Therefore, in order to have a better understanding of endemic fish distribution pattern in the upper Yangtze River, both land cover and characteristic river variables were integrated into the modeling in the present study.…”
Section: Introductionmentioning
confidence: 99%